Using cloud platforms in accounting: comparison of 1C and Xero - Atabayeva, A.K.; Akynov D.М.; Ovcharenko, I.A.; Agabekova, G.N.; Agabekova, Sh.N. (BUKETOV BUSINESS REVIEW, 2024)
Object: Research the effectiveness of using cloud platforms such as 1C: Accounting and Xero in the field of accounting and compare the quantity and quality of the tools presented. Methods: In working on the article, general methods of scientific knowledge were used: methods of empirical research (observation, comparison, analysis, synthesis (generalization); methods of theoretical research (ascending from the abstract to the concrete, from the general to the particular and from the phenomenon to the essence, identifying individual parts of the object, identification of cause-and-effect relationships); rules of formal logic; systematic approach. Findings: In order to understand the popularity and satisfaction of users of the Xero platform, the following indicators were studied: Average revenue per user (ARPU); Customer acquisition costs (CAC); Lifetime value (LTV) per subscriber; Churn (%). A low churn rate is a positive indicator indicating that customers are likely to stay. If your churn rate remains stable or decreases, it may indicate high customer satisfaction. An increase in lifetime value per subscriber indicates that customers are generating more revenue over the course of their relationship with the company. This can indicate long-term customer loyalty and satisfaction. An increase in ARPU may indicate that users not only remain, but are also willing to pay more for services, which may be due to increased satisfaction levels or the provision of additional value services. 1 C also has extensive capabilities, modularity, and is designed for different types of business, including production and trade. It has a multifunctional, localized interface and provides integration with various systems. The modular structure provides flexibility in selecting the required components. Based on the presented comparative analysis between Xero and 1C, it can be stated that both accounting systems have their own features and characteristics intended for different markets and audiences. Conclusions: The SWOT analysis revealed that 1C and Xero have their own unique advantages and limitations. 1C, with its extensive functionality and widespread adoption, is a powerful tool for companies seeking complete business process management. However, despite regular updates, its high complexity can require significant time and resources to master. On the other hand, Xero offers ease of use, cloud-based flexibility, and extensive integration capabilities. This makes it an ideal choice for small and medium-sized businesses, especially those who value mobility and real-time data availability.